Promoting Improved Livestock Development Practices for a Resilient Future - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The livestock production system contributes around 4% to India’s GDP and also serves as a source of income, food, and energy for the rural economy. Cattle, goat, and buffalo constitute the major share of livestock and are majorly present in states including Uttar Pradesh, Rajasthan Andhra Pradesh, and Madhya Pradesh. However, Cattle yields remain low and climate risks further impact livestock health as well as productivity. Weather events such as an increase in temperature, heatwaves, excess rainfall, drought exacerbate these problems and further increase the disease and mortality of cattle. As part of the project livestock development practices, services and technologies were promoted in the project districts (Betul- Madhya Pradesh, Nalanda- Bihar and Mathura, Uttar Pradesh) to reduce the vulnerability of livestock keepers against climatic variability. Present case study highlights the methodology and outputs achieved from these interventions.